FRI0009 Il4-10 synerkine: a novel anti-inflammatory drug to inhibit immunopathology in rheumatic diseases. (23rd January 2014) - Hartgring, S. A.; Steens-Louws, C.; de Smet, M.; Hack, E.; Van Roon, J. A.
Abstract : Background: A considerable percentage of patients shows a limited response to biologics targeting one specific inflammatory mediator, largely because of redundancy of these mediators. An attractive alternative is inhibition of multiple proinflammatory mediators and induction of immunoregulatory activity by regulatory cytokines such as IL4 and IL10. Many studies demonstrated the strong capacity of IL4 and IL10 as stand alone drugs to inhibit inflammation and tissue-destructive responses in animal and human in vitro models. Clinical results of these cytokines, however, have been disappointing, possibly because of poor bioavailability that is mainly due to their low molecular weight and rapid renal clearance. We have executed a feasibility study to develop IL4 and IL10 as one biologic, preserving distinct characteristics of each molecule plus improving bioavailablity by increasing the molecular size. Objectives: Development and testing of anti-inflammatory properties of an IL4/IL10 fusion protein; IL4-10 synerkine. Methods: IL4-10 synerkine was expressed in human HEK293 cells. Biochemical properties of IL4-10 synerkine were determined by western blot, size exclusion chromatography, and ELISA. Functional properties were studied by measuring the capacity of IL4-10 synerkine to regulate production of pro-inflammatory cytokines and their inhibitors, as well as proinflammatory and regulatory T cell activity, and expression Fcγ and Fcε receptors (FcεRI, IIa, IIb, III and FcεR). In addition, blocking IL4 receptor and IL10 receptor strategies were performed to confirm the specific activities of IL4 and IL10. Results: IL4-10 synerkine appeared as a glycosylated dimeric protein with a molecular size of 70kDa. ELISA as well as immunoblotting confirmed that the IL4-10 synerkine indeed consisted of IL10 and IL4 subunits. In whole blood assays IL4-10 synerkine dose-dependently inhibited multiple pro-inflammatory cytokines, which was almost complete at 20 ng/ml (IL1β, TNFα, IL6 and IL8, all p<0.001). This effect was dependent on interaction with IL10R and IL4R. Oppositely, the synerkine significantly induced production of IL1RA and preserved sTNFR levels. In addition, IL4-10 synerkine strongly inhibited Th1 and Th17 cytokine secretion, while maintaining FoxP3 expression and FoxP3-expressing CD4 T cells. Finally, while IL4 up regulated FcεR expression and IL10 up regulated expression of activating FcγRs on monocytes (all p<0.001), both Fcε and FcγR expression were largely down regulated to control levels in the presence of IL4-10 synerkine (all at least p<0.01). Conclusions: The IL4-10 synerkine is a novel anti-inflammatory drug that shifts multiple proinflammatory pathways towards immunoregulation. The increased molecular mass predicts better bioavailabilty in humans than the wild-type molecules, which potentially enhances its clinical efficacy. The strong and improved inhibitory activities of IL4-10 synerkine (as compared to IL4 or IL-10 monotherapy and combination therapy) that were observed in several animal models for inflammatory pain underscores the potential for treatment of inflammatory and possibly degenerative rheumatic diseases. Disclosure of Interest: None Declared